“DEAR SIS”: A Case Study on Trust Cultivation on Indonesian Facebook Online Craft Stores - Mayasari, Fitria; Khrisnamurti, Indra (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2019)
Advances in communications technology have allowed new forms of trade, i.e., through online means between sellers and customers. The use of the Facebook social networking platform as a tool for online business has questioned the factors influencing the creation of Trust among its users engaged in a community of craft makers (sellers and customers). This research hypothesized that three independent variables influence the Trust: the intensity of interaction, the similarity of interest, and endorsement—questionnaires distributed to 151 samples. Data analysis was performed through SPSS, using Spearman's correlation to note the strength of the relationship between variables. The results of the questionnaire show a medium-strength correlation between the independent and dependent variables. To cite this article (7th APA style): Mayasari, F. & Khrisnamurti, I. (2019). “Dear Sis”: A Case Study on Trust Cultivation on Indonesian Facebook Online Craft Stores. Journal Communication Spectrum, 9(2), 94-109. http://dx.doi.org/10.36782/jcs.v9i2.209